Anisotropic structural color particles from colloidal phase separation - Wang, Huan (Sci Adv, 2020)
Structural color materials have been studied for decades because of their fascinating properties. Effects in this area are the trend to develop functional structural color materials with new components, structures, or morphologies for different applications. In this study, we found that the coassembled graphene oxide (GO) and colloid nanoparticles in droplets could form component phase separations, and thus, previously unknown anisotropic structural color particles (SCPs) with hemispherical colloidal crystal cluster and oblate GO component could be achieved. The anisotropic SCPs, as well as their inverse opal hydrogel derivatives, were endowed with brilliant structural colors and controllable capabilities of fixation, location, orientation, and even responsiveness due to their specific structure, morphology, and components. We have also demonstrated that the anisotropic hydrogel SCPs with these features were ideal candidates for dynamic cell monitoring and sensing. These properties indicate that the anisotropic SCPs and their derivatives have huge potential values in biomedical areas.